Update of leadership-as-practice “practice theory”: Featuring Joe Raelin Interviewed by Jenny Robinson - Joseph A. Raelin; Jennifer L. Robinson (Leadership, 2022)
This article constitutes an interview between a new researcher of the field of Leadership-as-Practice (L-A-P), Jenny Robinson, with one of the co-creators of the field, Joe Raelin. It is dedicated to providing an update and refinement of leadership-as-practice “practice theory,” which has gone through a fair degree of transformation since this journal's first article on the subject in 2008. The call for such an update is precipitated by the need for emerging L-A-P researchers to appreciate the subject's conceptual boundaries for more consistent and integrated exploration. In particular, L-A-P claims to differentiate not only from other plural traditions in leadership but from other “as-practice” approaches in the wider management field. Some of the other distinctions covered in this article comprise the role of theory in L-A-P, its contribution to leadership research and leadership development, its connection to other related fields, and its phenomenological, ethical, democratic, and post-humanistic foundations.
Keywords: M51; M53; M54; 650; leadership-as-practice; practice theory; leadership; phenomenology; post-humanism; democratic leadership; social change; leadership development